Twist/untwist parameters are promising evaluators of myocardial mechanic changes in heart failure patients with preserved ejection fraction - Zhang, Yi; Li, Shen‐Yi; Xie, Juan‐Juan; Wu, Yuan (Clinical cardiology (Mahwah, N.J.), 2020)
Background This study aimed to evaluate the twist/untwist parameters of the left ventricle (LV) in patients with heart failure with preserved ejection fraction (HFpEF) measured by ultrasonic two‐dimensional speckle tracking echocardiography (STE) and to examine the correlations between twist parameters and serum N‐terminal pro b‐type natriuretic peptide (NT‐proBNP) as well as conventional two‐dimensional echocardiography (2DE) indexes. Hypothesis Changes in twist/untwist parameters can be used to evaluate LV function in HFpEF patients. Methods In 63 HFpEF patients and 40 healthy controls, we analyzed LV twist/untwist parameters by STE, cardiac function by 2DE, and serum NT‐proBNP by enzyme‐linked immunosorbent assay (ELISA). The correlations between twist/untwist parameters and 2DE parameters and serum NT‐proBNP were examined by Pearson correlation analysis. Results Left ventricular end diastolic inner diameter and ejection fraction in HFpEF patients were within the normal range, whereas other 2DE parameters including left ventricular posterior wall end diastolic thickness, interventricular septal thickness, left atrial volume index, E, E/A, and E/e' differed significantly between HFpEF patients and control subjects. The twist/untwist parameters such as peak apical rotation (Par), peak untwisting velocity (PUWV), and isovolumic diastole untwisting percentage (Iutw%) were significantly decreased in HFpEF patients compared with control participants. Positive correlations between PUWV/Iutw% and E/A/E/e' and a significant negative correlation between PUWV/Iutw% and left atrial volume index (LAVI) were observed. The plasma NT‐proBNP concentration was positively correlated with LAVI, but negatively correlated with PUWV and Iutw%. Conclusions Changes in twist/untwist parameters correlate well with conventional 2DE parameters and plasma levels of NT‐proBNP, and can be used to evaluate LV function in HFpEF patients. Par is sensitive to the LV myocardial function damage.